2013
DOI: 10.1186/2251-6832-4-30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of species, particle size and compacting pressure on relaxed density and compressive strength of fuel briquettes

Abstract: Reversible solid oxide cells can provide efficient and cost-effective scheme for electrical-energy storage applications. However, this technology faces many challenges from material development to system-level operational parameters , which should be tackle for practical purposes. Accordingly, this study focuses on developing novel robust artificial intelligence-based blackbox models to optimize operational variables of the system. A genetic-programming algorithm is used for Pareto modeling of reversible solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 9 publications
6
42
1
1
Order By: Relevance
“…The average particle size determined was 0.1466 mm for date palm trunk and of 2 mm for sawdust. These results confirmed that small particle sizes favor the densification of the material as this type of particles have greater surface area during the compaction, as already said in different studies [48,49]. Other reason, as mentioned, is the different lignin content of these two biomass feedstocks.…”
Section: Comparison Of Biomass Feedstockssupporting
confidence: 85%
“…The average particle size determined was 0.1466 mm for date palm trunk and of 2 mm for sawdust. These results confirmed that small particle sizes favor the densification of the material as this type of particles have greater surface area during the compaction, as already said in different studies [48,49]. Other reason, as mentioned, is the different lignin content of these two biomass feedstocks.…”
Section: Comparison Of Biomass Feedstockssupporting
confidence: 85%
“…For that purpose, a Coulter LS−230 laser light−scattering apparatus (BeckmanCoulter, Miami, FL) was used, being the average particle size determined of 0.1466 mm for date palm trunk and of 2 mm for sawdust. These results confirmed that small particle size could favor the densification of the material as this type of particles have greater surface area during the compaction, as already said in different studies [48,49]. Other reason, as mentioned, is the different lignin content of these two biomass feedstocks.…”
Section: Comparison Of Biomass Feedstockssupporting
confidence: 76%
“…The variability of biomass materials have resulted in inconsistency in the characteristics of fuel briquettes produced from different types of residues [8,57], this may even apply to the same type of residues grown at different season or different locations. It becomes necessary to understand the influence of the variability on biomass densification and fuel briquette's quality.…”
Section: Sample Batchmentioning
confidence: 99%
“…Briquettes manufactured at lower pressures of 30 to 60 MPa crumble easily, while those produced at higher pressures of 150 to 250 MPa remain compacted and durable [57], for example, increasing the compaction pressure from 1 to 10 MPa increased the shear strength of briquettes from 2.8 x 10 -2 kPa to 9.6 x 10 -2 kPa [43]. Currently, efforts are directed towards improving the quality of fuel briquettes produced at lower pressures.…”
Section: Pressurementioning
confidence: 99%